Printing Art with plastic from plants Printing Art with plastic from plants - da Silva Leote, Rosangela [UNESP] (Association for Computing Machinery (ACM), 2021)
This is a proposal for an exhibition of an artistic work to be assembled in this edition of ARTECH (2021). The work is called “Lux Cortina”. It is an interactive sculpture. Some considerations are made about the technologies and materials used in the production of sculptures and installations by this author. They are notes of methods to printing in 3D, with a minimum of commitment to the environment. Also is demonstrating the difficulties of moving away from the use products critical for the nature, when is used computer technologies. However, some options for reducing the impact for the environment are presented. The focus is printing with PLA thermoplastic (Polylactic Acid), which is made from plants, is biodegradable and fully recyclable, being in the category of bioplastics. The second focus is the use of materials that have a certain scale of friendliness, in certain contexts, such as silicon. To contextualize, is pointed out some uses those artists are making of 3D printing technologies, trying to indicate potentialities that collaboration between artists, architects and engineers can have, in terms of social, ecological, and global benefits for humanity, both for life on earth, as well as on other planets, like Mars.
Keywords: 3D Printing; Art installation; Bioplastic; Interactive object; Sustainability